Exotism in contemporary art: two art work - Borghi, Paula (Revista do Colóquio, 2021)
More and more, cosmogony and post-colonial studies contribute to the poetic and conceptual construction of artistic processes in Brazil, as well as to the exoticism concept and to the relationships between nature and culture. With this purpose, this paper (gender neutral) intend to analyze such discussion using two art work as a reference from Paulo Nazareth e Zé Carlos Garcia.
Keywords: Exoticism; Contemporary Art; Paulo Nazareth; Zé Carlos Garcia